Comparision on dynamic behavior of diesel spray and rapeseed oil spray in diesel engine - Sapit, Azwan; Razali, Mohd Azahari; Hushim, Mohd Faisal; Jaat, Norrizam; Mohammad, Akmal Nizam; Khalid, Amir (IOP Publishing, 2017)
Fuel-air mixing is important process in diesel combustion. It significantly affects the combustion and emission of diesel engine. Biomass fuel has high viscosity and high distillation temperature and may negatively affect the fuel-air mixing process. Thus, study on the spray development and atomization of this type of fuel is important. This study investigates the atomization characteristics and droplet dynamic behaviors of diesel engine spray fuelled by rapeseed oil (RO) and comparison to diesel fuel (GO). Optical observation of RO spray was carried out using shadowgraph photography technique. Single nano-spark photography technique was used to study the characteristics of the spray while dual nano-spark shadowgraph technique was used to study the spray droplet behavior. Using in-house image processing algorithm, the images were processed and the boundary condition of each spray was also studied. The results show that RO has very poor atomization due to the high viscosity nature of the fuel when compared to GO. This is in agreement with the results from spray droplet dynamic behavior studies that shows due to the high viscosity, the RO spray droplets are large in size and travel downward, with very little influence of entrainment effect due to its large kinematic energy.